The Effect of Transformational Leadership Style on Employee Performance At PT. Ciptamega Infrasana in Bogor - Rani Sujarwadi; Yayan Sudaryana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of transformational leadership style on employee performance at PT. Ciptamega Infrasana in Bogor. The method used is explanatory research with a sample of 72 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this research variable transformational leadership style obtained an average score of 3.811 with suitable criteria. Employee performance variable obtained an average score of 3.882 with suitable criteria. Transformational leadership style has a positive and significant effect on employee performance with a regression equation value of Y = 14.018 + 0.651X, and a correlation coefficient value of 0.778 or has a strong relationship with a determination value of 60.6%.